The social and solidarity economy in legal systems Provincials of Argentina - Torres, Miguel Agustín (Cooperativismo & Desarrollo, 2019)
Introduction: In the last decades the social and solidarity economy was installed, in Argentina, as an alternative of social and labor reintegration for certain groups of vulnerable populations. However, despite the growth of this trend and the articulation of different official policies aimed at supporting it, the legal coverage of the different aspects involved in the issue still lacks an adequate and symmetrical development. Thus, the normative scenario of the social economy reveals the initiative of some provincial states that advanced in the legal framework of the same. Methodology: the legal instruments on the social and solidarity economy of the provinces that progressed in the regulation of the subject are examined, textually and teleologically. Results: the legal recognition that the social and solidarity economy receives in the Argentine provincial systems is characterized. Conclusions: in a normative context determined by the absence of a specific national law, it is important to analyze the provincial legal texts on the subject, in order to describe the legal conception of the social and solidarity economy, to identify the actors that make up the sector and investigate the reception of social and solidarity principles in provincial legislation.